Baseline Plasma Metabotype Correlates With Direct-Acting Antiviral Therapy Nonresponse for HCV in HIV–HCV Coinfected Patients - Tripathi, Gaurav; Rooge, Sheetalnath; Yadav, Manisha; Mathew, Babu; Sharma, Nupur; Bindal, Vasundhra; Hemati, Hamed; Singh Maras, Jaswinder; Gupta, Ekta (Frontiers in Molecular Biosciences, 2022)
Abstract: Introduction: With the advent of direct-acting antiviral (DAA) therapy for HCV, cure is achieved at similar rates among co-infected as in HCV mono-infected patients. The present study evaluates host plasma metabolites as putative indicator in predicting the treatment response in baseline HIV-HCV patients. Methods: Non cirrhotic HIV-HCV (43) coinfected patients were treated with Sofosbuvir and Daclatasvir for 12 weeks. Plasma metabolite profiling pre and post therapy was analyzed in 20/43 patients. Of the 20 selected 10 (50%) attained the SVR (Responders) as defined by absence of HCV RNA at 12 weeks after the treatment and 10 (50%) didn't attained the cure for HCV (Non-responders). Results: A total of 565 features were annotated (metabolomic/spectral databases). Pre therapy, 39 metabolites differentiated (FC ±1.5, p<0.05) non-responders from responders. Of these 20 up- and 19 down-regulated were associated with tryptophan metabolism, nicotinamide metabolism and others. Post therapy, 62 plasma metabolite (12-up and 50-down, FC±1.5, p<0.05) differentiated non-responders from responders and highlighted significant increase in steroid, histidine metabolism and significant decrease in tryptophan metabolism, ascorbate, pyruvate metabolism in the non-responders. Based on random forest and multivariate linear regression analysis, baseline level of N-acetylspermidine (FC>2, AUC=0.940, Bfactor = -0.267) and 2- Acetolactate (FC>2, AUC=0.880, Bfactor = -0.713) significantly differentiate between non-responders from responders in HIV-HCV co-infection patients and were able to predict the failure of treatment response. Conclusion: Baseline increase in N-acetylspermidine and 2- Acetolactate levels is associated with likeliness of failure in attainment of cure for HCV in HIV-HCV co-infected patients.